Analisa Pengelolaan Kebutuhan Logistik Farmasi pada Instalasi Farmasi RS MBSD Periode Juli 2017- Juni 2018Analisa Pengelolaan Kebutuhan Logistik Farmasi pada Instalasi Farmasi RS MBSD Periode Juli 2017- Juni 2018Analisa Pengelolaan Kebutuhan Logistik Farmasi pada Instalasi Farmasi RS MBSD Periode Juli 2017- Juni 2018 - Suherman, Suherman; Nurwahyuni, Atik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
There is still a vacuum in the availability of medicines on a monthly basis, raising questions about how to manage pharmaceutical logistics in MBSD Hospital Pharmacy Installation. The purpose of this research is to find out how the logistics management system of drug supplies and various problems that occur at each stage of implementation in the MBSD Hospital Pharmacy Installation. This research uses descriptive and analytical methods that are quantitative and qualitative by conducting in-depth interviews, document review, and calculation of ABC drug classifications to then calculate the Economic Order Quantity value and Re Order Point time on drugs classified as category A critical index. On 571 types of drugs used in the period July 2017 to June 2018. On ABC usage there are 45 types of drugs classified as category A, in the ABC investment analysis there are 72 types of drugs including category A and the calculation of ABC Critical Index shows the number of drugs as many as 48 types classified as category A. The results of EOQ and ROP calculations on category A drugs from the ABC analysis of the Critical Index show results that can be considered by the MBSD Hospital to be used in evaluating drug supplies at the Pharmacy Installation.